The effects of process parameters for joining of AISI 1010-Cu alloys by friction welded - Caligulu, Ugur; Acik, Mustafa; Balalan, Zulkuf; Kati, Nida (Korean Soc Steel Construction-Kssc, 2015)
In this study, the effects of process parameters for joining of AISI 1010 low carbon steel and copper alloys by friction welded were investigated. Low carbon steel and commercial copper each of 12 mm diameter was used to fabricate the joints. The friction welding tests were carried out using a direct-drive type friction welding machine which was designed and manufactured for this purpose by us. After friction welding, in order to determine the microstructural changes that occurred, the interface regions of the welded specimens were examined by means of OM, SEM, EDS and X-Ray analysis. Microhardness and tensile tests were conducted to determine the mechanical properties of the welded specimens. The experimental results indicated that AISI 1010 low carbon steel could be joined to copper using the friction welding technique and for achieving a welding with a sufficient strength, the friction time has to be held as short as possible, while the rotational speed, friction and forging pressure has to be as high as possible. Tensile strength values also confirmed this result and at the interface did not occurred intermetallic phases. The maximum tensile strength of 294,67 MPa could be obtained for the joints welded under the welding conditions of rotation speed of 2300 rpm, friction pressure of 40 MPa, forging pressure of 80 MPa, friction time of 6 s and forging time of 3 s.
Keywords: AISI 1010; copper; friction welding; rotation speed; friction time